2021
DOI: 10.25105/psia.v2i2.10314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Konsep Tod Pada Kawasan Tod Dukuh Atas

Abstract: Jumlah penduduk di kota Jakarta yang meningkat setiap tahun memberikan dampak signifikan terhadap kebutuhan sistem transportasi. Oleh karena itu, sudah selayaknya untuk memperbaiki sistem perencanaan beserta infrastruktur pendukung transportasi agar tercipta kondisi kota yang teratur dengan menerapkan konsep pembangunan berorientasi transit atau Transit Oriented Development (TOD). TOD merupakan jenis pembangunan yang mengintegrasikan ruang kota dengan tujuan untuk menyatukan kegiatan, orang, bangunan dan ruang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…However, based on previous research, it was found that the pedestrian metric value in the Dukuh Atas TOD area still needs to be fully achieved. This is because pedestrian paths, bicycle lanes, and several other facilities still need to cover all available public road segments within a 500-m radius of the transportation stop point [26,27]. As a result, the TOD concept is expected to be an alternative or a solution for reducing Jakarta's level of congestion, one of which is the Dukuh Atas TOD area, which has become one of Jakarta's TOD-based regional developments [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, based on previous research, it was found that the pedestrian metric value in the Dukuh Atas TOD area still needs to be fully achieved. This is because pedestrian paths, bicycle lanes, and several other facilities still need to cover all available public road segments within a 500-m radius of the transportation stop point [26,27]. As a result, the TOD concept is expected to be an alternative or a solution for reducing Jakarta's level of congestion, one of which is the Dukuh Atas TOD area, which has become one of Jakarta's TOD-based regional developments [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This is because pedestrian paths, bicycle lanes, and several other facilities still need to cover all available public road segments within a 500-m radius of the transportation stop point [26,27]. As a result, the TOD concept is expected to be an alternative or a solution for reducing Jakarta's level of congestion, one of which is the Dukuh Atas TOD area, which has become one of Jakarta's TOD-based regional developments [26][27][28]. Furthermore, density is also one of the TOD principles in the 5Ds, but its applicability in the Dukuh Atas TOD area is still not suitable.…”
Section: Introductionmentioning
confidence: 99%